A 2.6‐g sound and movement tag for studying the acoustic scene and kinematics of echolocating bats. Issue 1 (11th November 2018) - Stidsholt, Laura; Johnson, Mark; Beedholm, Kristian; Jakobsen, Lasse; Kugler, Kathrin; Brinkløv, Signe; Salles, Angeles; Moss, Cynthia F.; Madsen, Peter Teglberg
Abstract: To study sensorimotor behaviour in wild animals, it is necessary to synchronously record the sensory inputs available to the animal, and its movements. To do this, we have developed a biologging device that can record the primary sensory information and the associated movements during foraging and navigating in echolocating bats. This 2.6‐g tag records the sonar calls and echoes from an ultrasonic microphone, while simultaneously sampling fine‐scale movement in three dimensions from wideband accelerometers and magnetometers. In this study, we tested the tag on an European noctula Nyctalus noctula during target approaches and on four big brown bats Eptesicus fuscus during prey interception in a flight room. We show that the tag records both the outgoing calls and echoes returning from objects at biologically relevant distances. Inertial sensor data enables the detection of behavioural events such as flying, turning, and resting. In addition, individual wing‐beats can be tracked and synchronized to the bat's sound emissions to study the coordination of different motor events. By recording the primary acoustic flow of bats concomitant with associated behaviours on a very fine time‐scale, this type of biologging method will foster a deeper understanding of how sensory inputs guide feeding behaviours in the wild.